A century of Repertorio Americano: from printed paper to the challenges of virtuality - Zamora-Cascante, Diego (2021)
This article briefly presents the history of Repertorio Americano during its 39-year cultural phase under the leadership of Joaquín García Monge. Next, the importance of the magazine as a publication of the Universidad Nacional is raised, as well as the need for García Monge’s legacy in relation to cultural dissemination and production to be part of the “necessary university”. Finally, the needs, challenges, and influence that Repertorio Americano suffereddue to the transformation of the cultural journal into an academic journal are studied, both in its cofiguration as a cultural , epistemological and printedproduct, and the current challenges. For this purpose, it is intended to make an analysis from the journal itself and not from the figure of its editor, since there is a diversity of studies on García Monge.